Genome-wide identification and functional characterization of WRKY transcription factors involved in the response to salt and heat stress in garlic (Allium sativum L). Issue 1 (1st January 2021) - Yang, Qing-Qing; Yang, Feng; Zhao, Yong-Qiang; Lu, Xin-Juan; Liu, Can-Yu; Zhang, Bi-Wei; Ge, Jie; Fan, Ji-De
Abstract: WRKY transcription factors (TFs) are primarily involved in regulating the response of plants to different types of abiotic stress and related physiological processes. WRKY genes have yet to be characterized in garlic ( Allium sativum L.), which is in the family Alliaceae. Here, 78 WRKY TFs were identified based on the garlic transcriptome and genome. They were divided into seven subfamilies based on Arabidopsis thaliana WRKY domains. Cis -element analysis revealed that the WRKY family members have ABRE and MBS cis -response elements that respond to salt stress, gibberellins, and drought stress. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis revealed that the expression of nine WRKY genes was induced under heat and salt stress.